2016
DOI: 10.1080/20550324.2016.1187966
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(ethylene terephthalate)/hyperbranched polymer nanocomposites by melt blending

Abstract: In this paper, nanocomposites of polyethylene terephthalate (PET) including polyesteramide-based hyperbranched polymer, or PET/Hyperbranched polymer nanocomposites, have been prepared via melt blending method with different hyperbranched polymer contents. In addition, morphology, surface structure, and thermal properties of these nanocomposites and virgin PET were studied by atomic force microscopy, attenuated total reflection fourier transform infrared spectroscopy and differential scanning calorimetry (DSC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Besides, amounts of nanoparticles higher than 0.4 wt. % negatively affects the mechanical properties of the nanocomposites, due to agglomeration of nanoparticles [30]. The possible formation of mechanical percolation networks with the RAF of rPET at interfacial regions with confined rPET matrix could justify these results above 0.4 wt.…”
Section: Dmta (Dynamic Mechanical Thermal Analysis)mentioning
confidence: 96%
“…Besides, amounts of nanoparticles higher than 0.4 wt. % negatively affects the mechanical properties of the nanocomposites, due to agglomeration of nanoparticles [30]. The possible formation of mechanical percolation networks with the RAF of rPET at interfacial regions with confined rPET matrix could justify these results above 0.4 wt.…”
Section: Dmta (Dynamic Mechanical Thermal Analysis)mentioning
confidence: 96%
“…45 The lower storage modulus of PET1-4 samples compared with PET0 at higher temperatures of 85 C is attributed by increasing the branched structure of the polymer matrix due to the addition of NPs. 57 It can be found that the amount of storage modulus of all samples increased during exposure to UV radiation (Figure 9b). The higher storage modulus value of the pure PET compared with the PET-based nanocomposites was because of the resistance of the PET0 against the changes in the crystallinity caused by UV radiation exposure.…”
Section: Dsc Testing Resultsmentioning
confidence: 88%
“…The decreases in T c of samples after UV radiation compared to similar samples before irradiation could be attributed to the breaking of some long PET chains, in which the broken short chains having stronger mobility. 57 The higher mobility of the broken molecules in the amorphous regions could cause them to rearrange T A B L E 3 The thermal parameters of PET-based nanocomposite films compared with the PET0 before and after being radiated for and re-crystallize, which, in turn, led to a slight increase in the X c of PET4 sample after UV radiation.…”
Section: Dsc Testing Resultsmentioning
confidence: 99%
“…At 75 °C, PEG 400 ‐DOPA showed viscosity values in the region of 3500 Pa s, with PEG 1000 ‐DOPA at 100 Pa s, PEG 2000 ‐DOPA at 1 Pa s, and GE‐DOPA at 200 Pa s, whereas PEG 200 ‐DOPA ranged at 5000 Pa s at 100 °C (Figure ). Taking into account that PEG 200 ‐DOPA and PEG 400 ‐DOPA are oligomers with molecular weights of 933 and 1103 Da respectively, the fact that they reach complex viscosity values between 3 and 5 kPa s (which compare to melt viscosity values of high molecular weight engineering polymers such as PET) is truly remarkable, and could only be attributed to robust non‐covalent interactions between their DOPA end‐groups. We have previously conducted similar rheological characterization of a related “control” poly(ester amide) based on l ‐phenylalanine ( M n = 7.9 kDa, T g = −18 °C, tested at 40 °C; no l ‐DOPA groups present), which indeed performed in a characteristic manner of a viscoelastic liquid, with complex viscosities of 2.0–3.0 kPa s across a similar frequency range.…”
Section: Resultsmentioning
confidence: 99%